Protective Effect of Poria Cocos Polysaccharides on Fecal Peritonitis-Induced Sepsis in Mice Through Inhibition of Oxidative Stress, Inflammation, Apoptosis, and Reduction of Treg Cells - Wu, Yu; Li, Dai; Wang, Han; Wan, Xiaojian (Frontiers in Microbiology, 2022)
This study was conducted to investigate the potential pharmacological effects of Poria Cocos polysaccharides (PCP) on fecal-induced peritonitis (FIP) mice. Consequently, the fecal peritonitis-induced septic mice with higher levels of TNF-α, IL-6, IL-1β, MDA, MPO, histopathological lesion and bacterial burden, lower levels of SOD and GSH. Interestingly, PCP-pre-treatment reduced inflammatory cytokines and oxidative stress in plasma and spleen and improved the resistance to fecal-induced peritonitis. Inflammatory infiltration and cell death in thymus or spleen tissue were alleviated with PCP pre-treatment. Furthermore, Treg cells were moderated in the spleen with PCP pre-administration. In addition, PCP pre-treatment down-regulated Annexin-V in the thymus of fecal peritonitis-induced septic mice, and apoptosis of splenic cells was dose-dependent. In conclusion, Poria Cocos polysaccharides have pharmacological and biological effects on fecal peritonitis-induced septic mice, and its molecular mechanism is related to anti-oxidative, anti-inflammation, anti-apoptosis, and the reduction of Treg activity in spleen cells.